Transfalcine Contusion Evacuation in Bifrontal Contusion - Singh, Anoop Kumar; Kumari, Gayatri; Dangat, Akash Rambhau (Indian Journal of Neurotrauma, 2025)
Traumatic bifrontal contusions have an unpredictable course with often rapid deterioration, requiring an aggressive approach. However, integral to an individual's personality, frontal lobe surgeries demand a maximally effective approach but with minimal invasiveness. The author explores the feasibility of a transfalcine corridor for the effectiveness of contusion evacuation in asymmetric bifrontal contusion cases, with one side extensive and the other moderate size, aiming minimal invasiveness on the less affected side without compromising the surgical efficacy. The authors have evaluated the role of transfalcine brain surgeries in the selected cases of bifrontal contusions, and here, they report the experiences of their first two cases performed using this corridor between January 2024 and April 2024 at their institution. Two cases of bifrontal contusions were operated on, with a sizeable contusion on one side and a relatively smaller basifrontal contusion on the other. The craniotomy was focused on the side with the larger contusion. After the contusion was evacuated from that side, the contralateral side was approached through a corridor made in the intervening falx cerebri, and the contralateral frontal contusion was evacuated under the microscope. Both patients showed significant clinical and radiological improvement in their postoperative period with early recovery. Transfalcine bifrontal contusion evacuation is a good option, especially in selected cases with one side larger and relatively smaller contralateral inferior-medial frontal contusion locations.
Keywords: transfalcine; bifrontal; basifrontal; contusion; frontal